Brain growth rate abnormalities visualized in adolescents with autism. Issue 2 (20th October 2011) - Hua, Xue; Thompson, Paul M.; Leow, Alex D.; Madsen, Sarah K.; Caplan, Rochelle; Alger, Jeffry R.; O'Neill, Joseph; Joshi, Kishori; Smalley, Susan L.; Toga, Arthur W.; Levitt, Jennifer G.
Abstract Autism spectrum disorder is a heterogeneous disorder of brain development with wide ranging cognitive deficits. Typically diagnosed before age 3, autism spectrum disorder is behaviorally defined but patients are thought to have protracted alterations in brain maturation. With longitudinal magnetic resonance imaging (MRI), we mapped an anomalous developmental trajectory of the brains of autistic compared with those of typically developing children and adolescents. Using tensor‐based morphometry, we created 3D maps visualizing regional tissue growth rates based on longitudinal brain MRI scans of 13 autistic and seven typically developing boys (mean age/interscan interval: autism 12.0 ± 2.3 years/2.9 ± 0.9 years; control 12.3 ± 2.4/2.8 ± 0.8). The typically developing boys demonstrated strong whole brain white matter growth during this period, but the autistic boys showed abnormally slowed white matter development (P = 0.03, corrected), especially in the parietal (P = 0.008), temporal (P = 0.03), and occipital lobes (P = 0.02). We also visualized abnormal overgrowth in autism in gray matter structures such as the putamen and anterior cingulate cortex. Our findings reveal aberrant growth rates in brain regions implicated in social impairment, communication deficits and repetitive behaviors in autism, suggesting that growth rate abnormalities persist into adolescence. Tensor‐based morphometry revealed persisting growth rate anomalies long after diagnosis, which has implications for evaluation of therapeutic effects. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.